Development of engobe coating compositions for clinker and facing bricks - Olena Khomenko; Nataliia Sribniak; Oleksandr Zaichuk (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2022)
This article deals with the basic principles of developing engobe compositions for facing and clinker ceramic bricks. The microstructure features of ceramic bricks have been studied, which must be considered when choosing the engobe composition and engobe products’ technology. The expediency of using alkaline and substandard kaolins as the main raw material, which improves the conditions for sintering ceramic coatings by applying the single annealing technology of construction ceramics, has been studied. Due to its higher annealing reactivity, compared to traditional clay materials, the experimental raw material in the engobe composition improves the adhesion of the coating to the ceramic base and increases the strength of the decorative and protective layer.